First synthesis of heterocyclic allenes – benzazecine derivatives. (10th February 2017) - Voskressensky, Leonid G.; Titov, Alexander A.; Dzhankaziev, Maksad S.; Borisova, Tatiana N.; Kobzev, Maxim S.; Dorovatovskii, Pavel V.; Khrustalev, Victor N.; Aksenov, Alexander V.; Varlamov, Alexey V.
Abstract : Benzazecines with an allene fragment were prepared for the first time and in high yields via tandem reaction of 1-phenylethynyl-1-methyl(benzyl)-1, 2, 3, 4-tetrahydroisoquinolines with activated alkynes in trifluoroethanol. Abstract : Benzazecines with an allene fragment were prepared for the first time and in high yields via tandem reaction of 1-phenylethynyl-1-methyl(benzyl)-1, 2, 3, 4-tetrahydroisoquinolines with activated alkynes in trifluoroethanol.